The ups and downs of global motion perception: a paradoxical advantage for smaller stimuli in the aging visual system - Hutchinson, Claire V.; Ledgeway, Tim; Allen, Harriet A. (Frontiers in Aging Neuroscience, 2014)
Recent evidence suggests that normal aging is typically accompanied by impairment in the ability to perceive the global (overall) motion of visual objects in the world. The purpose of this study was to examine the interplay between age-related changes in the ability to perceive translational global motion (up vs. down) and important factors such as the spatial extent (size) over which movement occurs and how cluttered the moving elements are (density). We used random dot kinematograms (RDKs) and measured motion coherence thresholds (% signal elements required to reliably discriminate global direction) for young and older adults. We did so as a function of the number and density of local signal elements, and the aperture area in which they were displayed. We found that older adults’ performance was relatively unaffected by changes in aperture size, the number and density of local elements in the display. In young adults, performance was also insensitive to element number and density but was modulated markedly by display size, such that motion coherence thresholds decreased as aperture area increased (participants required fewer local elements to move coherently to determine the overall image direction). With the smallest apertures tested, young participants’ motion coherence thresholds were considerably higher (~ 1.5 times worse) than those of their older counterparts. Therefore, when RDK size is relatively small, older participants were actually better than young participants at processing global motion. These findings suggest that the normal (disease-free) aging process does not lead to a general decline in perceptual ability and in some cases may be visually advantageous. The results have important implications for the understanding of the consequences of aging on visual function and a number of potential explanations are explored. These include age-related changes in spatial summation, reduced cortical inhibition, neural blur and attentional resource allocation.